SEISMIC VULNERABILITY ASSESSMENT OF FES MEDINA IN MOROCCO - S. Stefanini; L. Rovero; U. Tonietti (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2020)
The assessment of seismic vulnerability in the Maghreb area is not yet fully investigated, especially considering the important connection between the vulnerability and traditional housing or construction local types. This paper proposes a methodology for the assessment of seismic vulnerability at territorial scale that is calibrated on the specific characteristics of historical settlements in the North of Morocco, mostly made of patio buildings in aggregate. The proposed methodology is structured to be extended and replicated in other similar contexts and is based on the Vulnerability Index approach proposed by the National Group for Earthquake Defence (Gruppo Nazionale per la Difesa dai Terremoti, GNDT). This method was applied to the Medina of Fes, UNESCO World Heritage site, which has suffered severe damages from historical earthquakes. The study allowed the realization of vulnerability and fragility curves, damage scenarios for different seismic intensity and loss scenarios. The proposed methodology was applied a second time to the case study after a simulated structural retrofitting intervention. The results of this second application allowed to validate the guidelines and the reinforcement strategies calibrated on local construction culture. The results of the vulnerability assessment are also presented through maps in the Geographic Information System (GIS) environment.